Caribbean - Michener, James A. (James Albert), 1907-1997.; Browne, Roscoe Lee. ([United States] : Random House AudioBooks, 1989)
Novel about the Caribbean islands depicting pirate attacks, bloody slave revolts, and the Cuban revolution through a blend of fiction and history.
Only Michener could so masterfully bring the turbulent, dramatic history of the beautiful Caribbean to life. Moving from the European Courts of the 15th century that first claimed the region, to the Islands themselves, we watch the emergence of splendorous sugar plantations built on the backs of slaves; the bloody and victorious uprising in Haiti in 1800; and in modern times, the spread of the Rastafarian religion, the mass exodus from Cuba following the revolution and the general discontent of Caribbean nationales. Sprinkled throughout are fascinating portraits of historical heroes as they struggle against political, economic and racial oppression.
Abridged version of the book read by Roscoe Lee Browne.
Keywords: Caribbean Area -- History -- Fiction; Caribbean Area -- History -- Fiction